The balance of payments as a constraint on Turkey's growth, 1960 - 2004 - Secil Pacaci Elitok; Al Campbell (The University of Utah, Department of Economics, 2008)
The aim of this study is to test the existence of balance of a payments constraint on the long run economic growth of the Turkish economy. The balance of payments constrained growth (BPCG) model which was developed by Thirlwall (1979) and extended by Thirlwall and Hussain (1982) is tested over the period of 1960-2004 using OLS. Empirical findings of this paper support the BPCG model for the whole period under consideration. For the different sub-periods, there are either different essential economic relations or behaviors behind the BOP constraint.
Keywords: F14; F15; F41; F43; E12; 330; balance of payments constraint; Turkey; economic growth; international trade; elasticity; neo-liberalism; Wirtschaftswachstum; Außenwirtschaft; Zahlungsbilanz; Türkei